Radon and cancer mortality among underground uranium miners in the Příbram region of the Czech Republic. Issue 10 (9th August 2020) - Kelly‐Reif, Kaitlin; Sandler, Dale P.; Shore, David; Schubauer‐Berigan, Mary K.; Troester, Melissa A.; Nylander‐French, Leena; Richardson, David B.
Abstract: Background: This study aims to estimate the association between radon and site‐specific cancer mortality among a large contemporary cohort of male uranium miners. Methods: Annual occupational radon exposure was estimated based on a worker's duration of underground mining in a year and estimates of potential alpha energy of radon progeny in their location of work. Cancer mortality over the period 1977‐1992 was ascertained for a cohort of 16 434 male underground uranium miners employed in the Czech Republic between 1946 and 1992. Poisson regression was used to estimate relationships between cumulative radiation exposure (in working level months [WLM]) and site‐specific cancer mortality. Results: Radon is positively associated with lung cancer mortality (excess relative rate [ERR] per 100 WLM = 0.2; 95% confidence interval [CI]: 0.10, 0.37). The best fit of the dose‐response relationship between radon and lung cancer mortality was linear and estimates of radon‐lung cancer associations varied by windows of time‐since‐exposure. Positive associations between radon and several types of cancer other than lung cancer were identified, notably chronic lymphocytic leukemia (CLL) (ERR/100 WLM = 0.24; 95% CI: [not determined [ND], 5.10]) and extrathoracic cancer (ERR/100 WLM = 0.12; 95% CI: [ND, 0.69]). We observed no associations between radon and stomach cancer, nor between radon and several hematopoietic cancer subtypes. Conclusions: This study confirms the established radon‐lung cancer association and suggests that radon may also be associated with other types of cancer mortality. Further investigations of extrathoracic and CLL cancer, with the aim of obtaining more precise estimates, are warranted to understand associations between radon and cancers other than lung.